A Slow Food termékek, mint a vidék valódi értékei - Panyor, Ágota (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The primary aim of the international movement which started in the middle of the I980’s in Italy, was to control the effects destroying the traditions generated by the fast-food restaurants and the globalization, and slow down the world. The members of this movement made an appointment about directing the people’s attention to preserve the national culture by using traditional foods and foodstuffs, and they are trying to slow down the globalizationed world. In spite of this in our country the movement hasn’t spread especially and it doesn’t move enough people to participate.